«En engi má við skǫpum vinna»: Individual Agency and Structural Determination in Vǫlsunga Saga - Barreiro, Santiago Francisco; Martin Paez, Mario
The purpose of this article is to analyze the relationship between decision making and contextual determination in Volsunga Saga, produced in Iceland or Norway during the 13th Century. We will show that social and kinship structures impose obligations that individuals normally accept as something inexorable. We will see that the influence of structure pressure is manifested not only in the physical qualities of the individuals, but also in their personal behavior. Our aim is to demonstrate that structural constraints are compared to the inexorability of destiny and the destructive character of greed and the doom treasure of Andvari. Finally, we will discuss how the idea of intentionality is explored in the saga and may justify certain actions that go against social expectations. It will be argued that these dynamics run parallel to the theology of intention present in the Christian thought and reflect the efforts of the saga author to insert his narrative in a wider ideological context. El propósito de este artículo es analizar la relación entre la toma de decisiones y determinaciones contextuales representadas en Vëlsunga Saga, producida en Islandia o Noruega durante el siglo XIII. Mostraremos que la estructura social y el sistema de parentesco imponen obligaciones que los individuos aceptan normalmente como algo inexorable. Veremos que la influencia de la presión estructural se manifiesta no solo en las cualidades físicas de los individuos, sino también en sus comportamientos. Nuestro objetivo es demostrar que las constricciones estructurales son comparadas con la inexorabilidad del destino y el carácter destructivo de la codicia y del tesoro maldito de Andvari. Finalmente, discutiremos cómo la idea de intencionalidad es explorada en la saga y puede justificar ciertas acciones que van en contra de las expectativas sociales. Argumentaremos que estas dinámicas están relacionadas con la teología de la intención presente en el pensamiento cristiano y refleja los esfuerzos del autor de la saga por insertas su ...